Długoterminowa polityka podatkowa w przedsiębiorstwie - Kwiecińska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Knowledge of taxes and tax law is essential under free-market economy for two main reasons. Firstly, taxes constitute an essential legal instrument of the state's influence on its subordinated subjects. Secondly, the possession of due tax knowledge enables to adapt to legal solutions and to minimize taxation detriments. For those reasons, tax education is essential not only for a company but also for the whole society. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 181-186